Лексичките иновации во прозата на Малески и нивниот статус во стандардниот македонски јазик - Јаnusheva, Violeta (Mundo Eslavo, 2015)
Immediately after the codification of the Macedonian language, in 1945, the Dictionary of the Macedonian language with Serbo-Croatian interpretation appeared showing the high level of stability of the Macedonian language’s lexicon and of its standardization. А lot of authors with their language expression, through actualization of national lexemes and through innovations in the process of word formation, contributed to the affirmation of the Macedonian language as a means of creating prime works of art. The language of an art work cannot be separated from the social context in which it is written. It cannot be separated from the national language too, because the language of an art work reflects the whole lexicon of the language. The article analyzes certain lexical items present in the novel “Razboj” of the Macedonian writer V. Maleski, which are determined as lexemes that actualized national lexis and word formation innovations in Panoska’s doctoral thesis, regarding their meaning and their utilization in the Macedonian standard language today, and confirms that they lost the status they had in this period. It shows that the lexis as a part of the language system is constantly subjected to changes. The paper reveals lexemes which can be used as instances when elaborating chapters of the Macedonian lexicology.